2018
DOI: 10.1016/j.anr.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Influencing Factors of Metabolic Syndrome Among Persons with Physical Disabilities

Abstract: The major risk factors for metabolic syndrome among persons with physical disabilities were obesity and older age. Performing physical activity was associated with a lower risk of metabolic syndrome. Therefore, we recommend using a continuous obesity management program and physical activity to prevent metabolic syndrome among persons with physical disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Carmelli et al found that the consistency rates of diabetes, hypertension and obesity in identical twins were significantly higher than those in fraternal twins, indicating that genetic factors have an important relationship with the occurrence of MetS [21]. Current smoking status was a risk factor for MetS, which was consistent with previous studies [22,23]. Compared with never consumed alcohol, moderate alcohol consumption led to a lower risk of developing MetS, and this was consistent with the findings of Tresserra-Rimbau [24].…”
Section: Discussionsupporting
confidence: 87%
“…Carmelli et al found that the consistency rates of diabetes, hypertension and obesity in identical twins were significantly higher than those in fraternal twins, indicating that genetic factors have an important relationship with the occurrence of MetS [21]. Current smoking status was a risk factor for MetS, which was consistent with previous studies [22,23]. Compared with never consumed alcohol, moderate alcohol consumption led to a lower risk of developing MetS, and this was consistent with the findings of Tresserra-Rimbau [24].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, pain and dysfunction of the knee joint will inevitably lead to reduction in an individual's physical activity, resulting in fat accumulation and aggravated energy metabolism disorders, which further exacerbate IR and MetS. 34 A significant finding of the current study was that the METS-IR was positively related to some adipokines and inflammatory markers. The expression levels of CRP, ESR, leptin, adiponectin, and resistin in the plasma and the leptin level in the SF were all significantly associated with METS-IR.…”
Section: Discussionmentioning
confidence: 61%
“…It was found that frequent alcohol consumption contributed to a higher prevalence of MetS and its medical consequences in China [ 12 ] and Spain [ 35 ]. A Korean National Health Insurance Service-National Sample Cohort revealed that the major risk factors for MetS among individuals with physical disabilities were unhealthy lifestyle habits, obesity, and older age [ 36 ]. There was a significant dose–response relationship across beverage types, increasing apolipoprotein, adiponectin, and cholesterol levels [ 37 ].…”
Section: Discussionmentioning
confidence: 99%